The Correlation Between Neonatal Intensive Care Unit Safety Culture and Quality of Care. Issue 4 (December 2020) - Profit, Jochen; Sharek, Paul J.; Cui, Xin; Nisbet, Courtney C.; Thomas, Eric J.; Tawfik, Daniel S.; Lee, Henry C.; Draper, David; Sexton, J. Bryan
Abstract : Objectives: Key validated clinical metrics are being used individually and in aggregate (Baby-MONITOR) to monitor the performance of neonatal intensive care units (NICUs). The degree to which perceptions of key components of safety culture, safety climate, and teamwork are related to aspects of NICU quality of care is poorly understood. The objective of this study was to test whether NICU performance on key clinical metrics correlates with caregiver perceptions of safety culture. Study Design: Cross-sectional study of 6253 very low-birth-weight infants in 44 NICUs. We measured clinical quality via the Baby-MONITOR and its nine risk-adjusted and standardized subcomponents (antenatal corticosteroids, hypothermia, pneumothorax, healthcare-associated infection, chronic lung disease, retinopathy screen, discharge on any human milk, growth velocity, and mortality). A voluntary sample of 2073 of 3294 eligible professional caregivers provided ratings of safety and teamwork climate using the Safety Attitudes Questionnaire. We examined NICU-level variation across clinical and safety culture ratings and conducted correlation analysis of these dimensions. Results: We found significant variation in clinical and safety culture metrics across NICUs. Neonatal intensive care unit teamwork and safety climate ratings were correlated with absence of healthcare-associated infection ( r = 0.39 [ P = 0.01] and r = 0.29 [ P = 0.05], respectively). None of the other clinical metrics, individual or composite, were significantly correlated with teamwork or safety climate. Conclusions: Neonatal intensive care unit teamwork and safety climate were correlated with healthcare-associated infections but not with other quality metrics. Linkages to clinical measures of quality require additional research. Abstract : Supplemental digital content is available in the text.